2009
DOI: 10.1038/emboj.2009.272
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of endosomal clathrin and retromer-mediated endosome to Golgi retrograde transport by the J-domain protein RME-8

Abstract: After endocytosis, most cargo enters the pleiomorphic early endosomes in which sorting occurs. As endosomes mature, transmembrane cargo can be sequestered into inwardly budding vesicles for degradation, or can exit the endosome in membrane tubules for recycling to the plasma membrane, the recycling endosome, or the Golgi apparatus. Endosome to Golgi transport requires the retromer complex. Without retromer, recycling cargo such as the MIG‐14/Wntless protein aberrantly enters the degradative pathway and is depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
234
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(252 citation statements)
references
References 62 publications
13
234
1
4
Order By: Relevance
“…This leads to increased MIG-14 degradation and reduced steady-state levels of the MIG-14 protein (12)(13)(14). Consistent with the idea that loss of the TOCA proteins also leads to missorting of MIG-14 into the degradative pathway, we found that more MIG-14-GFP colocalized with late endosome and lysosome marker tag RFP-RAB-7 in toca double mutant animals than in WT animals (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…This leads to increased MIG-14 degradation and reduced steady-state levels of the MIG-14 protein (12)(13)(14). Consistent with the idea that loss of the TOCA proteins also leads to missorting of MIG-14 into the degradative pathway, we found that more MIG-14-GFP colocalized with late endosome and lysosome marker tag RFP-RAB-7 in toca double mutant animals than in WT animals (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 85%
“…hTfR and hTAC recycle to the plasma membrane via recycling endosomes, also known as the endocytic recycling compartment (4,7). MIG-14 recycles to the TGN, but previous work had not tested whether MIG-14 transits the recycling endosome en route to the Golgi (12)(13)(14).…”
mentioning
confidence: 99%
“…Although it has been suggested that the budding of clathrincoated vesicles contributes to endocytic recycling, a flat clathrin lattice on endosomes has been suggested to create and/or maintain degradative subdomains on endosomes associated with HRS and ESCRT proteins, regulating the sorting of ubiquitinated cargo proteins in the endosome (44)(45)(46). Thus, another possibility is that ACAPs could interact with clathrin in the flat lattice to affect the balance in degradation and recycling that must be maintained in the endosomal system.…”
Section: Discussionmentioning
confidence: 99%
“…S6 B and C) as hTAC-positive tubular structures. As a comparison, localization of MIG-14, another endogenous CDE cargo (42)(43)(44), was confined to vesicular structures and was not altered in sec-10 mutants (Fig. S6 B and D).…”
Section: Dual Involvement Of Sec-10 In Apical and Basolateral Endosomalmentioning
confidence: 99%